Eksplorasi persepsi dan motivasi tentang pembelajaran daring : implikasinya terhadap kinerja guru matematika - Supriadi, Edi (International Journal of Progressive Mathematics Education, 2024)
Purpose: This study aims to analyze the relationship between teachers' perceptions of online learning and work motivation on the performance of junior high school mathematics teachers. 2. Design/methodology/approach: A quantitative approach was employed using simple and multiple linear regression. The sample included 113 mathematics teachers in Kuningan Regency, selected via cluster random sampling from a population of 127. 3. Findings: The results demonstrate a significant positive correlation between perception, work motivation, and teacher performance. The data met normality and homogeneity requirements, suggesting that constructive perceptions and robust motivation effectively mitigate technical constraints in digital environments. 4. Practical implications: These findings provide a basis for policymakers to prioritize psychological aspects and work motivation to sustain high-quality mathematics instruction. 5. Originality/value: This study offers a unique contribution by integrating technological perception and internal motivation as primary determinants of mathematics teacher performance within the post-pandemic online learning framework. Purpose: Penelitian ini bertujuan menganalisis hubungan antara persepsi guru terhadap pembelajaran daring dan motivasi kerja terhadap kinerja guru matematika di tingkat SMP. Design/methodology/approach: Menggunakan pendekatan kuantitatif dengan teknik regresi linear sederhana dan berganda. Sampel terdiri dari 113 guru matematika di Kabupaten Kuningan yang dipilih melalui cluster random sampling dari total populasi 127 guru. 3. Findings: Hasil uji menunjukkan hubungan positif signifikan antara persepsi dan motivasi kerja terhadap kinerja guru. Data berdistribusi normal dan homogen, mengindikasikan bahwa persepsi yang konstruktif dan motivasi yang kuat efektif mengatasi keterbatasan teknis dalam lingkungan daring. Practical implications: Temuan ini memberikan dasar bagi pengambil kebijakan untuk fokus pada penguatan aspek psikologis dan motivasi kerja guna menjaga kualitas pembelajaran matematika yang berkelanjutan. Originality/value: Studi ini memberikan kontribusi unik dengan mengintegrasikan persepsi teknologi dan motivasi internal sebagai determinan utama kinerja guru matematika dalam konteks pembelajaran daring pasca-pandemi.